Two new species of Apateticinae from Guangxi, China (Coleoptera: Staphylinidae) - Chang, Jin-Kang; Schillhammer, Harald; Tang, Liang (Zootaxa, 2025)
Two new species of Apateticinae from Guangxi, southern China are described: Apatetica xuyuhaoi Chang, Schillhammer & Tang, sp. nov. and Nodynus huapingensis Chang, Schillhammer & Tang, sp. nov. These species are characterized, and compared to similar congeners, supplemented with illustrations of the habitus and sexual characters.